The Effectiveness of Dollar Cost Averaging - Summary and Critiques of the literature review - Chen, Kun (2007)
Recently, dollar cost averaging has gained popularity in the stock market investment. Compared with traditional investment strategy lump sum, some academics argue it can reduce investment risk without sacrificing much return. However, there are increasingly more studies question its effectiveness and argue it has no value. Due to the controversial viewpoints on its effectiveness, this study aims to investigate whether this investment strategy is superior to the traditional strategy lump sum. The summary and critiques of the literature review is the main focus in this dissertation. There are three academic viewpoints on DCA it is a superior strategy, it is an inferior strategy, it can be both superior and inferior, compared with alternative strategies LS, VA, BH or Bal. However, all of these studies have shortcomings and should be questioned. After the criticism, I conclude that DCA is inferior to LS in most cases. It is an inferior investment strategy to LS in terms of risk-return trade-off, utility, transaction costs, and dividends, and is not effective when investing in bond market. It performs badly under the behavioural framework of prospect theory and price anomalies but has advantages in hedging against regrets and facilitating self-control. However, it can be superior to LS when the average period and investment horizon is short and when prices for volatile stocks tend to move downward. In addition, it can also be a desirable strategy for high risk-averse investors. Furthermore, the period between February and September is the best time for implementing DCA investment.